2005
DOI: 10.1097/01.aids.0000168973.59466.14
|View full text |Cite
|
Sign up to set email alerts
|

Nelfinavir and nevirapine side effects during pregnancy

Abstract: Nelfinavir- or nevirapine-containing HAART regimens during pregnancy are well tolerated. Side effects of antiretroviral therapy are more frequent in pregnant than in non-pregnant women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
40
1
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 18 publications
5
40
1
2
Order By: Relevance
“…Some authors suggested that antiretroviral-drug-related side effects are more frequent for some AIDS-associated retroviruses in pregnant than in nonpregnant HIV-infected women (14). Our study regimen was well tolerated, with no severe adverse events reported.…”
mentioning
confidence: 62%
“…Some authors suggested that antiretroviral-drug-related side effects are more frequent for some AIDS-associated retroviruses in pregnant than in nonpregnant HIV-infected women (14). Our study regimen was well tolerated, with no severe adverse events reported.…”
mentioning
confidence: 62%
“…The careful monitoring for hepatotoxicity after initiation of ARV therapy is important since it has been demonstrated that the side effects of ARV therapy are more frequent in pregnant than in non-pregnant women. This situation is more often demonstrated with the use of nevirapine [12,13].…”
Section: Discussionmentioning
confidence: 98%
“…Las reacciones tóxi-cas pueden aparecer entre los 10 y los 280 días de iniciado el tratamiento (23)(24)(25)(26). La hepatotoxicidad se ha presentado en pacientes con edad entre los 18 y 45 años (21, 24-27), con elevación de las transaminasas y rash (23,(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37). Se presentó 1 caso de ductopenia, caracterizado por un tipo de lesión colestásica (25).…”
Section: Valoración De La Aparición De Hepatotoxicidadunclassified
“…Se presentó 1 caso de ductopenia, caracterizado por un tipo de lesión colestásica (25). El manejo se fundamenta en la suspensión de la nevirapina y cambio en la farmacoterapia (23,(26)(27)(28)(29). La frecuencia de hepatotoxicidad por este medicamento es variable, entre el 0,5% y el 20% (24,30,31,34,(37)(38)(39).…”
Section: Valoración De La Aparición De Hepatotoxicidadunclassified